Predicting the potential distribution of major marine mammals in the Cosmonaut Sea - Yufei Dai; Fanyi Meng; Fuxing Wu; Xing Miao; Denghui Yan; Mingding Zhong; Shunan Cao; Yuli Wei; Longshan Lin (Frontiers in Marine Science, 2025)
The Southern Ocean, a critical marine region on Earth, is undergoing significant environmental changes due to global climate change, including reductions in sea ice extent, ocean acidification, and alterations in the Antarctic Circumpolar Current (ACC). The Cosmonaut Sea, notable for its dynamic sea ice and rich biological activity, remains one of the least explored regions in the Southern Ocean, with limited data on its marine mammal populations. This study conducted during the 38th Chinese National Antarctic Research Expedition (CHINARE) from January to March 2022, collected systematic data on marine mammal occurrences. Species distribution modeling (SDM) was used to assess the influence of environmental variables on the distribution of the most abundant marine mammal species observed in the Cosmonaut Sea, including humpback whales ( Megaptera novaeangliae ), crabeater seals ( Lobodon carcinophaga ), and Antarctic minke whales ( Balaenoptera bonaerensis ). Our results indicated significant performance variations among the different algorithms, with ensemble model yielding more accurate predictions. Environmental variables such as water depth, sea surface height, and mixed layer thickness were identified as significant factors influencing habitat suitability for different species. Humpback whales were found to have the widest distribution range, followed by Antarctic minke whales and crabeater seals. Generally, the study provides the first comprehensive analysis of marine mammal distribution in the Cosmonaut Sea, highlighting the effectiveness of ensemble models in ecological predictions. The findings emphasize the importance of integrating high-resolution data and incorporating predator-prey interactions in future studies to improve our understanding and conservation of these complex ecosystems.